1993
DOI: 10.1073/pnas.90.2.447
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid transmembrane domains and lateral diffusion in fibroblasts.

Abstract: The lateral diffusion of fluorescent phospholipids in cultured Chinese hamster lung fibroblasts was examined by modulated fringe pattern photobleaching. When cells were labeled and maintained at 7C, the fluorescence remained localized at the plasma membrane. N-[6-(7-Nitrobenz-2-oxa-1,3-diazol-4-yl-amino)caproyllsphingosylphosphocholine (C6-NBD-SphPCho) and 1-acyl-2-[6-(7-nitrobenz-2-oxa-1,3-diazol-4-yl-amino)caproylJ phosphatidylcholine (C6-NBDPtdCho) both diffused with the same apparent lateral diffusion coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Thus lower local microviscosity (Morrot et al, 1989;Tanaka and Ohnishi, 1976) and a faster lateral diffusion (Morrot et al, 1986;Rimon et al, 1984) have been ascribed to the lipids in the cytoplasmic erythrocyte leaflet. Similar properties exist also in other cells, such as fibroblasts (El-Hage Chahine et al, 1993). Studies with artificial membranes reconstituted from the characteristic phospholipids of each monolayer demonstrated that differences in microviscosity and diffusibility were primarily due to the phospholipid composition of the membrane (Cribier et al, 1990).…”
Section: Intracellular Organellesmentioning
confidence: 65%
See 1 more Smart Citation
“…Thus lower local microviscosity (Morrot et al, 1989;Tanaka and Ohnishi, 1976) and a faster lateral diffusion (Morrot et al, 1986;Rimon et al, 1984) have been ascribed to the lipids in the cytoplasmic erythrocyte leaflet. Similar properties exist also in other cells, such as fibroblasts (El-Hage Chahine et al, 1993). Studies with artificial membranes reconstituted from the characteristic phospholipids of each monolayer demonstrated that differences in microviscosity and diffusibility were primarily due to the phospholipid composition of the membrane (Cribier et al, 1990).…”
Section: Intracellular Organellesmentioning
confidence: 65%
“…Apparently, this absence of diffusion might be explained by sphingomyelin-cholesterol interactions, as depleting the erythrocyte membrane in cholesterol stimulated sphingomyelin transmembrane movement (our unpublished data). This absence of sphingomyelin diffusion was also detected in other cells, namely hamster fibroblasts (El-Hage Chahine et al, 1993).…”
Section: Relation Between Movement and Asymmetrymentioning
confidence: 69%
“…We noted that the plasma membrane-associated lifetime of C6-NBD-PS is slightly shorter than that of C6-NBD-PC. This might be explained again by the fact that a significant fraction of the PS analogue has been transported to the cytoplasmic leaflet sensing the reduced lipid packing of this leaflet as previously shown by biochemical and biophysical studies (36,37).…”
Section: Flim Is Suitable To Detect Transient Small Lipid Domains-mentioning
confidence: 95%
“…Taking into account that a lateral diffusion coefficient of 10 Ϫ7 cm 2 /s is an upper estimate, domains resolvable by FLIM could be even smaller. Typical values for lateral diffusion of lipid analogues in plasma membranes are between 1 ϫ 10 Ϫ9 cm 2 /s and 5 ϫ 10 Ϫ9 cm 2 /s as measured for fibroblasts (36) and red blood cells (37), respectively. Hence, FLIM should be appropriate to capture even very small lipid domains as long as they are stable for at least 30 ns.…”
Section: Flim Is Suitable To Detect Transient Small Lipid Domains-mentioning
confidence: 99%
“…This marked and unexpected stability in the labeling of the plasma membrane we are describing for the vascular endothelium, with no significant probe internalization, appears to be very useful for the present study. It is another example that the balance between plasma membrane labeling and probe internalization can strongly vary from one cell type to the other (Martin and Pagano, 1987;El Hage Chahine et al, 1993;Kok et al, 1990;Kobayashi and Arakawa, 1991 ;Sleight and Abanto, 1989).…”
Section: Discussionmentioning
confidence: 99%